Advanced Magnetic Nanocomposites Structural, Physical Properties and Application - Yadav, Raghvendra Singh (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of research articles and review articles, which was published in the Special Issue "Advanced Magnetic Nanocomposites: Structural, Physical Properties and Application". This book ''Advanced Magnetic Nanocomposites: Structural, Physical Properties and Application'' discussed recent development on advanced magnetic nanoparticles and nanocomposites with detailed explanation of structural and physical characteristics, and further possible potential application.